Finite element analysis of the high-temperature creep deformation of a TZM heavy duty charge carrier. (November 2015) - Valentini, B.; Leuprecht, C.; Plankensteiner, A.; Sigl, L.S.
Abstract: Due to its outstanding combination of properties, e.g. high electrical and thermal conductivity, low coefficient of thermal expansion and high rupture as well as high creep strength, the molybdenum alloy TZM is widely used in high-temperature applications. The creep deformation behavior due to transient thermal and charge-induced mechanical loading of a TZM heavy duty charge carrier for a high-temperature sintering furnace, is analyzed numerically with the ABAQUS finite element package. All structural parts of the assembly of the sheet-based charge carrier including joining elements such as screws and rivets are modeled. The creep behavior of the refractory metal components is accounted for by a rate-dependent constitutive material model which takes into account both the dislocation- as well as the diffusion-based regime. The fully coupled thermo-mechanical analysis safely detects failure-prone locations, and allows design improvements prior to the physical realization of assembly prototypes. Highlights: A rate-dependent constitutive material model for describing the creep strains in the secondary creep regime is proposed. Within the secondary creep regime the creep model accounts for dislocation as well as diffusion creep. The creep model parameters are derived by fitting the model to experimental data of TZM. The creep model is used for computing the transient high-temperature deformation behavior of a TZM heavy duty charge carrier.